Interrelation between the lipid accumulation product index and diabetic kidney disease in patients with type 2 diabetes mellitus - Tang, Min; Yao, Shuangshuang; Cao, Han; Wei, Xiaohui; Zhen, Qin; Tan, Yijiong; Liu, Fang; Wang, Yufan; Peng, Yongde; Fan, Nengguang (Frontiers in Endocrinology, 2023)
Objective: The purpose of this study was to determine the relation between the lipid accumulation product index (LAPI) and diabetic kidney disease (DKD) in patients with type 2 diabetes mellitus (T2DM). Methods: Herein, 931 patients were enrolled and their data were collected. Then the interrelation between LAPI and DKD was assessed using multivariate logistic regression analyses (LRAs) and by a restricted cubic spline (RCS). Results: In total, 931 participants (352 females and 579 males) aged 55 years on average were included in the study. After adjusting for several confounders, the odds ratio for DKD was increased evidently in the third LAPI tertile compared with that in the first LAPI tertile. In addition, the RCS revealed a positive interrelation between LAPI and DKD. In the subgroup analyses, age, sex, hyperlipidemia, hypertension, and HbA1c did not significantly interact with LAPI. Conclusions: LAPI was higher in the DKD group than in the no-DKD group, and LAPI is positively linked with DKD, which may have potential value to diagnose DKD in clinical practice.